RESEARCH OF BUSINESS SUBJECTS AS A PREREQUISITE FOR THEIR DETINIZATION - Pyskun, L. (Municipal economy of cities. Series: «Economy science», 2023)
The article is devoted to the definition of the main directions of research of business entities, their qualifications and state of development during the war period, taking into account the prerequisites of their detinization and the detinization of the economy of Ukraine as a whole. Attention is focused on discrepancies in the qualifications of business entities in the legislation of Ukraine. The main qualification criteria of business entities are described. It was determined that, thus, 1) micro-enterprises are enterprises with a book value of assets up to 350,000 euros, net income from the sale of products (goods, works, services) up to 700,000 euros. EUR, total cumulative income up to EUR 2 million. euros and with an average number of employees up to 10; 2) small enterprises with a book value of assets up to 4 million euros, net income from the sale of products (goods, works, services) up to 8 million euros, a total aggregate income of up to 10 million euros and with an average number of employees up to 50; 3) medium - with a book value of assets up to 20 million euros, net income from the sale of products (goods, works, services) up to 40 million euros, a total aggregate income of up to 50 million euros, an average number of employees up to 250; 4) large: book value of assets over 20 million euros, net income from sales of products (goods, works, services) over 40 million euros, total aggregate income over 50 million euros, average number of employees over 250 people. A comparative analysis of the number of operating enterprises by types of economic activity was carried out, with a division into large, medium, small and micro enterprises. Prospects of the research directions have been determined: analysis and adaptation of business entities in war and post-war times; development of a recommendation on the detinization of business entities; as well as the justification of proposals for the implementation of a number of measures, the involvement of non-refundable financial support and technologies for the reconstruction and modernization of enterprises, the provision of affordable loans, the localization of equipment production in the state, etc.